Details of SARS-CoV-2 reinfections at a major UK tertiary centre. Issue 6 (June 2021) - Garvey, Mark I.; Casey, Anna L.; Wilkinson, Martyn A.C.; Ratcliffe, Liz; McMurray, Claire; Stockton, Joanne; Holden, Elisabeth; Osman, Husam; Loman, Nick J
Highlights: There remains uncertainty surrounding reinfection with SARS-CoV-2. The 'second wave' of transmission in the UK offered an opportunity to examine this. We observed reinfections in our patients, whole genome sequencing implied variants not previously identified in wave 1 were responsible for these recent infections. Further studies are required to define the true impact of reinfections. Real time whole genome sequencing will be useful to rapidly identify new variants within the hospital setting to facilitate appropriate management of patients.